Examining Students' Attitudes Towards iPads as Interactive Multimedia Tools and their Impact on Learning Quality in Indonesian Private Secondary School - Mahnun, Nunu; Subaidi, Subaidi; Arsyad, Junaidi; Faruq, Umar (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores students' attitudes toward using iPads as interactive multimedia tools in learning Islamic education (PAI) and examines the impact of this approach on learning quality. With the growing integration of technology in education, understanding the effects of interactive multimedia like iPads on students' learning experiences is critical. A mixed-methods approach was employed, involving both quantitative and qualitative analysis. A sample of 123 students from grades 7 to 9 was selected through stratified random sampling from a school that uses iPads in its learning system. Additionally, ten students were purposively chosen for interviews based on varying levels of iPad engagement. Quantitative data were analyzed using descriptive statistics and regression analysis, while qualitative data were analyzed thematically. The findings indicated that students generally had a positive attitude toward using iPads in PAI learning. In both quantitative and qualitative assessments, students described the iPad-based learning as "fun," "interesting," "flexible," and preferred over traditional textbooks. Regression analysis revealed a significant positive effect of students' attitudes on PAI learning quality (Sig = 0.000 0.05). Qualitative data further showed that using iPads improved comprehension, learning effectiveness, and outcomes. The positive attitudes toward iPads suggest that interactive multimedia can enhance student engagement and learning in PAI. This study highlights how the use of iPads positively impacts both the learning process and outcomes, supporting more effective Islamic education. This research demonstrates that students’ positive attitudes toward iPads significantly improve the quality of PAI learning. The findings underscore the importance of incorporating interactive multimedia tools like iPads in teaching to enhance student learning experiences.